PERENCANAAN PERSEDIAAN MATERIAL DENGAN PEMILIHAN METODE LOT SIZING YANG OPTIMAL PADA BATCHINGPLANT PT. X - Nuh Akbar; A'isyah Salimah (Construction and Material Journal, 2020)
Inventory is one of the asset / investment in a company that can be either raw materials, work in process, and finished goods, the primary function is to ensure the smooth supply of goods demand mechanism according to the needs of customers/consumers. Companies often have problems of inventory, supplies of which the company a shortage of inventory which could disrupt the smooth implementation of production, so that these problems could make the company down. Therefore, inventory planning is needed to obtain minimum inventory costs. Material requirements planning is done using with the Lot sizing, using MRP method that begins with forecasting the master production schedule for the coming period of one year. Based on the pattern of data, forecasting techniques used trend line analysis model and exponential smoothing with trend adjustment model. By finding out the material requirement data, product structure and bill of materials, lead time and inventory costs for materials, we could make a comparison of the cost of inventory planning by using 2 lot sizing techniques, there are fixed order quantity (FOQ) and period order quantity (POQ). This method is applied in PT. X to supply raw materials ready mix concrete, and of the both methods were chosen methods that produce the most optimum cost. Based on the analysis, period order quantity (POQ) technique result the minimum total inventory cost is IDR. 112,705,080.96. Keywords : Inventory, Forecasting, MRP, Lot Sizing, Optimum Inventory Cost.